Proceedings - compendio : Tecnology, innovation and production for sustainable development
Summary report - Final conclusions of forums and chapters - Summaries of some keynote addresses - Selected papers of participants - Development of the congress and exhibition (synthesis in spanish) - World congress authorities - Institutional references - Sponsors - Pictures of the congress and exhibition.